Long-Run Relationships and Causality Tests Between Military Expenditure and Economic Growth in India - Khalid, Masoud Ali; Mustapha, Alhaji Bukar (The Economics and Finance Letters, 2014)
Economists recognize that the public expenditure has an impact on economic growth. The rising level of military spending over other classes of public expenditure like economic and social services has raised a serious concern among scholars and have been at the core of recent development literature and thinking. In this study, we focus on to reexamine the effects of military spending on economic growth in India using annual data from the period of 1980 to 2011. The analysis is carried out within a multivariate setting that includes real GDP, real government military expenditure, population and real export.. In this paper, the autoregressive distributive lags (ARDL) cointegration approach is used to reexamine the long-run relationships among the variables. We then employ the Granger causality test to identify the direction of causality. The results for ARDL tests indicate that there is a significant relationship between military expenditure and economic growth in the short run, while the long run results suggest otherwise. While the estimated granger causality outcomes, revealed a unidirectional relationship between GDP and military spending.